Multiplane ultrasound approach to quantify pleural effusion at the bedside - Remerand, Francis; Dellamonica, Jean; Mao, Zhang; Ferrari, Fabio [UNESP]; Bouhemad, Belaid; Yang Jianxin; Arbelot, Charlotte; Lu, Qin; Ichai, Carole; Rouby, Jean-Jacques (Springer, 2010)
To assess the accuracy of a multiplane ultrasound approach to measure pleural effusion volume (PEV), considering pleural effusion (PE) extension along the cephalocaudal axis and PE area.Prospective study performed on 58 critically ill patients with 102 PEs. Thoracic drainage was performed in 46 patients (59 PEs) and lung computed tomography (CT) in 24 patients (43 PEs). PE was assessed using bedside lung ultrasound. Adjacent paravertebral intercostal spaces were examined, and ultrasound PEV was calculated by multiplying the paravertebral PE length by its area, measured at half the distance between the apical and caudal limits of the PE.Ultrasound PEV was compared to either the volume of the drained PE (59 PE) or PEV assessed on lung CT (43 PE). In patients with lung CT, the accuracy of this new method was compared to the accuracy of previous methods proposed for PEV measurement. Ultrasound PEV was tightly correlated with drained PEV (r = 0.84, p < 0.001) and with CT PEV (r = 0.90, p < 0.001). The mean biases between ultrasound and actual volumes of PE were -33 ml when compared to drainage (limits of agreement -292 to +227 ml) and -53 ml when compared to CT (limits of agreement -303 to +198 ml). This new method was more accurate than previous methods to measure PEV.Using a multiplane approach increases the accuracy of lung ultrasound to measure the volume of large to small pleural effusions in critically ill patients.
Keywords: Pleural effusion; Critical care; Ultrasound imaging; Computed tomography scan; Pleural drainage